(untitled) (Alternautas, 2023)
The articles in this issue provide a variety of perspectives on recent transformations in the Amazon. The first set of articles focuses on the relationship between capital, the state, and indigenous communities and movements. They explore the different political mechanisms, conflicts, and quandaries that emerge from extractivism in the Amazon. The second set of articles analyzes and documents the socio-environmental impacts faced by indigenous communities in the Amazon region. They illustrate different forms of resistance and community resilience mechanisms, as well as indigenous artistic activism in the Amazon. This issue concludes with an interview for the Dialogues section and two book reviews.